Transforming Kempo Fitness: Enhancing Physiological Responses and Physical Performance in Adolescents via a Tabata-Based Method - Nurkholis; Aghus Sifaq; Andri Suyoko; Waristra Tyo Nirwansyah; Bayu Agung Pramono; Raden Roro Shinta Arisanti (OVS LLC, 2023)
Study purpose. Examining the physiological and physical effects of Tabata training with Kempo sports movement techniques. Materials and methods. The study participants were 16 adolescents divided into two distinct groups: the Tabata group and the non-Tabata group. The training was conducted for 6 weeks, 3 times per week, with each session lasting 2 hours. The training components for kicks and punches included Gyaku Geri, Jun Mawashi Geri, Jun Zuki, and Gyaku Mawashi Geri. Each teenager did physical exercise once a week for 2 hours. A normality test (Shapiro-Wilk) was used to assess the normality of the data. A Two-Way ANOVA with a significance level of less than 0.05 was conducted to examine the difference in means between the two groups. Furthermore, the researchers also tested the N-Gain Score to assess the effectiveness of the 6-week Tabata training program. All tests were conducted using SPSS version 23 and GraphPad Prisma version 10 for graph creation. Results. The statistics indicate that a 6-week training with Tabata can effectively reduce resting heart rate and improve Standing Broad Jump (SBJ) performance by a value of sig. <0.05. In the pretest-posttest difference test within the group, the results show sig. <0.05. The results of the N-Gain Score test show that Kempo training using the Tabata method is effective in reducing resting heart rate by up to 88%, but is not effective in increasing power (SBJ) by a value of 10%. Conclusions. The study revealed that incorporating the Tabata method into Kempo training, with necessary adjustments for 6 weeks, led to a notable reduction in resting heart rate. A decrease in resting heart rate is a dependable indicator of the advancement in physical fitness and general well-being in adolescents.